1988
DOI: 10.1007/bf00172629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trazodone on the sleep of depressed subjects ? a polygraphic study

Abstract: The effects of 400400 mg trazodone on the sleep patterns of ten depressed in-patients treated for 5 weeks were studied during the initial (days 1-3) and terminal (days 26-28) treatment periods. The sleep parameters were compared to those obtained from three sleep recordings performed just prior to the initiation of the treatment and after 2 adaptation nights at the end of a 2-week drug-free period. At the same time, the clinical evolution of patients was evaluated weekly using MADRS and Hamilton-Anxiety scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 12 publications
4
51
0
Order By: Relevance
“…In our study, the patients did not use trazodone at doses higher than 100 mg/day, which may have contributed to a lower effectiveness when compared to mirtazapine. There appears to be some improvement in sleep parameters with increasing doses of trazodone 6,7,10 . Nierenberg and colleagues reported good in subjective sleep parameters (PSQI -Pittsburgh Index) with the use of 50 mg/day of trazodone while evaluating patients with secondary insomnia with the use of antidepressants 24 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, the patients did not use trazodone at doses higher than 100 mg/day, which may have contributed to a lower effectiveness when compared to mirtazapine. There appears to be some improvement in sleep parameters with increasing doses of trazodone 6,7,10 . Nierenberg and colleagues reported good in subjective sleep parameters (PSQI -Pittsburgh Index) with the use of 50 mg/day of trazodone while evaluating patients with secondary insomnia with the use of antidepressants 24 .…”
Section: Discussionmentioning
confidence: 96%
“…Trazodone has proved to be effective in the treatment of sleep disorders in depressed patients (not always older) [6][7][8] , in secondary sleep disorders when compared to other substances 9,10 and in healthy individuals 11 . Assessments of the clinical response to trazodone hydrochloride for the treatment of sleep disorders in demented patients may contribute to the pool of therapeutic options for these patients.…”
mentioning
confidence: 99%
“…This study, however, used substantially lower doses of trazodone than Scharf and Sachais [112] and nearly half the dose of the studies of Mouret et al [111]. Although no laboratory assessment of sleep was included, Jacobsen [114] reported improved subjective sleep with the co-administration of trazodone in 20/21 depressed patients who had MAOI-associated insomnia and 26/27 patients with insomnia but who were treated with other psychotropic medications.…”
Section: Trazodonementioning
confidence: 99%
“…In an early report, Mouret et al [111] showed no evidence of decreased REM sleep time in 10 depressed patients treated for 5 weeks with trazodone. Sleep assessments were conducted at baseline and again at the end of treatment.…”
Section: Trazodonementioning
confidence: 99%
“…The effects of trazodone (400-600 mg) on the sleep patterns of 10 depressed inpatients were studied over a treatment period of 5 weeks [63]. At the beginning of treatment, there was an increase in TST and sleep stage 2 (absolute), and a decrease in sleep stage 1, sleep latency and in the number of awakenings.…”
Section: Trazodonementioning
confidence: 99%